Dead poets' property—how does copyright influence price?. (9th February 2018) - Li, Xing; MacGarvie, Megan; Moser, Petra
Abstract: Copyrights create long‐lived intellectual property in goods ranging from science, literature, and music to news, film, and software. The economic effects of copyright, however, are difficult to identify in modern settings. This article exploits an unintended differential increase in copyright length under the UK Copyright Act of 1814—in favor of books by dead authors—to examine the effects of longer copyright terms on price. We find that a doubling in copyright length was associated with a substantial (roughly 50%) increase in the price of books. Additional years of copyright improved publishers' ability to practice intertemporal price discrimination.